Nest provisioning with parasitized caterpillars by female potter wasps: costs and potential mechanisms. (June 2022) - Leduc, Sarah; Rosenberg, Tamir; Johnson, Alfred Daniel; Segoli, Michal
Abstract : Females of the potter wasp Delta dimidiatipenne collect caterpillars from the surrounding vegetation and place them inside their mud-constructed nest cells to provision their offspring. It has been observed that females frequently collect caterpillars that are already internally parasitized by the larvae of the gregarious parasitoid wasp Copidosoma primulum . In such cases, the potter wasp offspring's food supply may become depleted, and they may fail to complete their development, while the C. primulum offspring mature but remain trapped and eventually die within the mud cell. This raises the question: why do potter wasp females continue bringing parasitized caterpillars into their nests? We aimed at quantifying the fitness costs of this behaviour, while investigating the potential mechanisms sustaining it. For this, we conducted a field survey of Heliothis nubigera caterpillars, the most common prey of D. dimidiatipenne, from the nest cells and from the nearby vegetation. These were used to estimate the parasitism rate and, in laboratory experiments, to quantify the cost of feeding and developing on parasitized caterpillars, as well as the response of parasitized versus nonparasitized caterpillars to a simulated predator attack. We found that potter wasp larvae that were provisioned with parasitized caterpillars had reduced developmental success. Early potter wasp larval stages were indeed less likely to feed efficiently when provided with a single parasitized caterpillar compared to a nonparasitized one. Despite these costs, we found that female potter wasps seem to collect parasitized caterpillars more frequently than expected according to their occurrence in the vegetation. We found that parasitized caterpillars reached a higher body mass and were less active in their response to a simulated predator attack. These characteristics might contribute to the presumed attractiveness and higher susceptibility of parasitized caterpillars to the predatory potter wasps. Highlights: D. dimidiatipenne females often provision their nests with parasitized caterpillars. As a result, their offspring suffer reduced developmental success. Parasitized caterpillars reach a higher mass than nonparasitized ones. Parasitized caterpillars are less responsive to a simulated predator attack. These characteristics may make them more susceptible to predation by potter wasps.